Penerapan Pembelajaran Collaborative Problem Solving untuk Meningkatkan Self-Concept Mahasiswa - Johannis Takaria (Pattimura University, 2018)
The focus of this research is to comprehensively analyze the differences in self concept improvement of Primary School teacher candidates in terms of early mathematical ability (KAM). This difference analysis is facilitated using collaborative problem solving (CPS) model, with Quasi Experimental research method and designed with Nonequivalent Pretest-Posttest Control Group type. The study sample involved 60 PGSD students in academic year 2016/2017. Identified through the results of the study that there is a difference in the increase of self-concept of student statistics, where the group of students who get the lectures with the CPS model get a higher increase than the group of students using expository learning (EPS), both whole students and based on the level of early mathematical ability (KAM) . This improvement difference is due to the effective use of CPS model. Collaborate in static lectures can improve student's positive self concept because in the transformation process there is an exchange of creative ideas among students.